Parathyroidectomies: Pre and Post Op Usage of Calcium Supplementation and Effect on Calcium Levels - Goonewardene SS; Ready A (Archives of Renal Diseases and Management - Peertechz Publications, 2016)
Introduction: PTH is released from the parathyroid glands behind the thyroid and is the primary regulator of calcium homeostasis. Indications for surgery in hyperparathyroidism remain controversial but  can  include  symptomatic  disease,  renal  stones,  impaired  renal  function,  bone  involvement  or marked  reduction  in  bone  density.  Due  to  hypocalcaemia  post  op,  pre-op  calcium  loading  should occur. However not much research has been conducted into this area. Methods: We retrospectively reviewed notes of patients with hyperparathyroidism secondary to renal failure admitted to a single centre, single surgeon, for parathyroidectomies. The following were determined: calcium preloading (type and dose) in secondary hyperparathyroidism, average calcium level  on  admission  and  post  op,  for  preloaded  and  non-loaded  secondary  hyperparathyroid  cases.This  was  also  determined  for  primary  hyperparathyroidism  and  renal  transplant  cases.  Notes  were also  reviewed  for  oral  calcium  supplementation  or  IV  calcium  supplemenyation  (type  and  average dose), for preloaded/ non preloaded cases, primary cases and new transplants. Length of stay was also reviewed. Statistical differences will be calculated.